Effect of cadmium on 24-hour pattern in expression of redox enzime and clock genes in rat medial basal hypothalamus - Jiménez Ortega, Vanesa (2010)
Fil: Jiménez Ortega, Vanesa. Universidad Complutense. Facultad de Medicina. Departamento de Bioquímica y Biología Molecular III; España